Energy efficiency, information, and the acceptability of rent increases: A multiple price list experiment with tenants - Lang, Ghislaine; Lanz, Bruno (MIT CEEPR working paper 2018-014, 2018)
This paper studies the role of imperfect information and attentional biases in the context of energy efficiency investments in rented properties and associated split incentives. We design a multiple price list experiment representing owners’ decision to replace the central heating appliance, and employ both within-subject information disclosure and between-subject variation in information provision to quantify how tenants trade-off energy efficiency and rent increases. A set of quantile regressions suggests that information on expected energy bills reduction induces around 30% of tenants to equate financial savings and acceptable rent increase. Around 20% of tenants oppose rent increase and do not respond to information, whereas tenants’ valuation in the upper tail of the distribution exceeds financial savings, presumably on account of pro-environmental motives. By contrast, information on energy bills variability dampens acceptable rent increase. Our results highlight the importance of realistic ex-ante estimates of financial savings associated with energy efficiency investments.
Keywords: Market failures; Information; Split incentives; Energy efficiency; Environmental policy; Rented properties; Economic experiments; Multiple price lists.